PERAN MATA KULIAH PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK MAHASISWA UIN SYAHADA PADANGSIDIMPUAN - Riska Adinda Putri Siregar; Uci Wardiana Harahap; Sulham Efendi Hasibuan (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study aims to analyze the role of the Islamic Religious Education (Pendidikan Agama Islam/PAI) course in fostering students’ moral character at Syekh Ali Hasan Ahmad Addary State Islamic University of Padangsidimpuan. Moral development has become an important issue in higher education along with the increasing moral and social challenges faced by students. This research employed a qualitative approach with a phenomenological design to explore students’ subjective experiences related to the internalization of moral values through PAI learning. Data were collected through in-depth interviews with 15 students from the Islamic Religious Education study program who had completed the PAI course. Data analysis was conducted using thematic analysis, including data reduction, data display, and conclusion drawing. The results indicate that the PAI course plays a significant role in shaping students’ moral character, particularly in instilling values such as honesty, responsibility, discipline, tolerance, and academic ethics. Students perceive PAI as a moral and spiritual guideline that helps direct their behavior in academic and social life. Factors influencing the effectiveness of moral development include lecturer quality, learning methods, campus environment, and students’ motivation. Therefore, PAI makes an important contribution to holistic student character development. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran mata kuliah Pendidikan Agama Islam (PAI) dalam pembinaan akhlak mahasiswa di Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Pembinaan akhlak menjadi isu penting dalam pendidikan tinggi seiring dengan meningkatnya tantangan moral dan sosial di kalangan mahasiswa. Penelitian ini menggunakan pendekatan kualitatif dengan desain fenomenologis untuk menggali pengalaman subjektif mahasiswa terkait internalisasi nilai-nilai akhlak melalui pembelajaran PAI. Data dikumpulkan melalui wawancara mendalam terhadap 15 mahasiswa Program Studi Pendidikan Agama Islam yang telah menempuh mata kuliah PAI. Analisis data dilakukan menggunakan analisis tematik melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa mata kuliah PAI berperan signifikan dalam membentuk akhlak mahasiswa, terutama dalam menanamkan nilai kejujuran, tanggung jawab, disiplin, toleransi, serta etika akademik. Mahasiswa memaknai PAI sebagai pedoman moral dan spiritual yang membantu mengarahkan perilaku dalam kehidupan akademik dan sosial. Faktor yang mempengaruhi efektivitas pembinaan akhlak meliputi kualitas dosen, metode pembelajaran, lingkungan kampus, serta motivasi mahasiswa. Dengan demikian, PAI memiliki kontribusi penting dalam pembinaan karakter mahasiswa secara holistik.